ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA KOPERASI SIMPAN PINJAM SWAMITRA CITRA NIAGA SAMARINDA TAHUN 2014-2016 - -, Febri Damaswati (EKONOMIA, 2019)
Companies in carrying out working capital activities tend to increase and decrease. In a previous research it has been described that source and usage of working capital at Cooperative Swamitra Citra Niaga Samarinda in year 2012-2013 increased, but within of 3 periods (2014-2016) working capital not always an increase. As though company, cooperative Swamitra Citra Niaga Samarinda in terms of working capital will increase or decrease from one period to the next periode with various causes underlying the change in working capital. The purpose of this writing is to know and analysis the source and usage of working capital at the Cooperative Swamitra Citra Niaga Samarinda in year 2014 – 2016 with the formulation of the problem is whether the source and usage of working capital is 2014-2016 has increased and what the factors are caused increased the source and usage of working capital in year 2014-2016.The used of basic theory is managemet accounting that focuses on the source and usage of working capital. Hypothesis or a provisional suspicion of this research that the source usage of working capital at the Cooperative Swamitra Citra Niaga Samarinda in year 2014 – 2016 has increased.The used of analytical tools are balance sheet comparasion analysis, working capital change report and usage of working capital.The results of the study concluded that the report source and usage of working capital at the Cooperative Swamitra Citra Niaga Samarinda has increased, this the hypothesis is accepted.